CHARACTER DEVELOPMENT STRATEGIES IN SCHOOLS: A LITERATURE REVIEW - Novianty Djafri; Abdul Wahab Syakhrani (Indonesian Journal of Education (INJOE), 2025)
This study reviews various character development strategies in schools based on existing literature. The main focus is on holistic approaches that integrate moral values into the curriculum and extracurricular activities, as well as the importance of the teacher's role as a role model in students' character development process. It was found that the direct integration of character values in subjects and the provision of practical platforms for students to apply these values are highly effective in shaping students' character. In addition, training and support for teachers in classroom management and character-based teaching contributed significantly to the success of the programme. Continuous evaluation and monitoring is an important process to ensure that the strategies implemented remain relevant and effective. In conclusion, collaboration between curriculum integration, teachers' roles, and continuous evaluation can create a school environment that supports comprehensive student character development